2021
DOI: 10.1108/mf-06-2020-0331
|View full text |Cite
|
Sign up to set email alerts
|

Do investors herd in emerging economies? Evidence from the Indian equity market

Abstract: PurposeThe purpose of this study is to empirically examine the presence of herding behavior of Indian investors using daily sample data drawn from the Standard and Poor's (S&P) Bombay Stock Exchange-500 Index over the period 2007–2018.Design/methodology/approachThe study employs the model proposed by Chang et al. (2000), taking stock return dispersion as a measure to capture herding. The empirical results demonstrate the absence of herding behavior in all market states, that is, normal, up and down market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…stated that most continental nations experienced a strong herding effect during the global financial crisis, and Nordic nations also experienced it during the Eurozone crisis Bekiros et al (2017). observed that under extreme market conditions, herding becomes highly pronounced Ansari and Ansari (2021). stated that herding is absent in all market conditions Demirer and Kutan (2006).…”
mentioning
confidence: 99%
“…stated that most continental nations experienced a strong herding effect during the global financial crisis, and Nordic nations also experienced it during the Eurozone crisis Bekiros et al (2017). observed that under extreme market conditions, herding becomes highly pronounced Ansari and Ansari (2021). stated that herding is absent in all market conditions Demirer and Kutan (2006).…”
mentioning
confidence: 99%